Residual energy dispersal fracturing: A newly proposed term for fractures propagating from sharp‐force trauma. Issue 1 (30th January 2023) - Tamminen, Heather M.; Ford, Andrew L. J.; Welham, Kate; Loe, Louise; Webb, Helen; Boyle, Angela; Smith, Martin J.
Abstract: Objectives: The identification and interpretation of skeletal trauma is an important topic in osteoarchaeology, forensic anthropology and palaeosciences. Trauma analysis is a fast‐moving sub‐discipline with constantly evolving methodological approaches. This paper describes the process of a particular form of fracturing that propagates specifically from the floor of cut marks and proposes new terminology for this subset of fractures. Materials and Methods: This terminological gap was identified during the re‐examination of remains from a minimum of 52 decapitated individuals (52 post‐cranial and 47 cranial remains) found in a mass grave from the 10th–11th century CE on Ridgeway Hill near Weymouth in Dorset (UK) in 2009. Originally analyzed by Oxford Archaeology Ltd., all individuals in this collection were re‐appraised using digital technology to test new techniques for this study. Results: During this investigation, it has become apparent that the length of chop marks can be overestimated during some conventional analysis because the chop transitions into a fracture propagating from the floor of the chop mark. Discussion: To increase awareness of these fractures, the term residual energy dispersal (RED) fractures is proposed as these are distinct from other radiating fractures arising from sharp‐blunt‐force trauma. The ability to distinguish RED fractures from others has the potential to contribute to the identification of previously unidentified chop marks and to the interpretation of events surrounding an injury. Research Highlights: The term "Residual Energy Dispersal" (RED) fracturing is proposed for fractures propagating from the base of a cut mark in sharp‐force or sharp‐blunt‐force trauma analysis. These fractures can make chop marks look longer than they truly are and therefore they can impact the interpretation of the events that caused the trauma.